The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1111/1541-4337.13084
|View full text |Cite
|
Sign up to set email alerts
|

Natural and low‐caloric rebaudioside A as a substitute for dietary sugars: A comprehensive review

Abstract: For health and safety concerns, traditional high-calorie sweeteners and artificial sweeteners are gradually replaced in food industries by natural and low-calorie sweeteners. As a natural and high-quality sugar substitute, steviol glycosides (SvGls) are continually scrutinized regarding their safety and application. Recently, the cultivation of organic stevia has been increasing in many parts of Europe and Asia, and it is obvious that there is a vast market for sugar substitutes in the future. Rebaudioside A, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 232 publications
0
7
0
Order By: Relevance
“…Responses in terms of animal weight increase and/or feed use efficiency vary based on the animal species and physiological stage, as well as the length of the feeding trial, the type of FW, and the substitution rate [ 125 ]. A number of studies found no difference when comparing diets with substitution with diets without substitution [ 126 , 127 , 128 ]. On the other hand, other studies found that diets with substitution caused poultry [ 129 ] and pigs [ 130 ] to gain less weight.…”
Section: Meat Quality and Animal Growthmentioning
confidence: 99%
“…Responses in terms of animal weight increase and/or feed use efficiency vary based on the animal species and physiological stage, as well as the length of the feeding trial, the type of FW, and the substitution rate [ 125 ]. A number of studies found no difference when comparing diets with substitution with diets without substitution [ 126 , 127 , 128 ]. On the other hand, other studies found that diets with substitution caused poultry [ 129 ] and pigs [ 130 ] to gain less weight.…”
Section: Meat Quality and Animal Growthmentioning
confidence: 99%
“…Unlike pure enzyme reactions or whole-cell reaction systems, microbial cell factories are limited in the case of SG production because of the rate-limiting steps involving CYP450s; the accumulation of intermediate metabolites leads to cytotoxicity or growing pressure, as well as the imbalance of the metabolic network [ 3 , 79 ]. Recently, a study used an engineered S. cerevisiae strain to produce 1368.6 mg/L and 132.7 mg/L of rubusoside and rebaudiosides (Reb A, Reb D, and Reb M), respectively, from glucose in 15 L bioreactors [ 11 ].…”
Section: Biosynthesis Of Glycosidesmentioning
confidence: 99%
“…14 The main components of SGs are stevioside, followed by rebaudioside A (Reb A) and Reb C. 14,15 Due to their high sweetness with low-calorie value and no safety concerns, SGs are increasingly used as food additives to help control the consumption of sugar. 16 Nevertheless, whether SGs have a beneficial impact on glucose metabolism in adults remains unclear. While some randomized controlled trials (RCTs) showed promising effects of SGs on reducing blood glucose levels, 17,18 others did not reveal significant effects.…”
Section: Introductionmentioning
confidence: 99%
“…14 The main components of SGs are stevioside, followed by rebaudioside A (Reb A) and Reb C. 14,15 Due to their high sweetness with low-calorie value and no safety concerns, SGs are increasingly used as food additives to help control the consumption of sugar. 16…”
Section: Introductionmentioning
confidence: 99%